Why won't the pathologist give me a diagnosis? Interpreting uncertainty in head and neck pathology reports. Issue 5 (June 2022) - Stephens-LaBorde, I.S.; Brierley, D.J
Abstract: Pathology reports often contain elements of uncertainty, and communication between clinicians and pathologists is paramount for providing the best patient care. Surveys were given to pathology service-users and pathologists to ascertain confidence levels regarding certain phrases used in pathology reports. A focus group then met with pathologists to gain insight into why certain phrases are used and the challenges that are faced in presenting an uncertain diagnosis. Whilst most of the phrases were interpreted similarly between service-users and pathologists, some elicited more variation in confidence than others, suggesting that the message conveyed in pathology reports is not always interpreted the way it is intended to be.